"I've never told anyone this before": Co‐constructing intimacy in sex and sexualities research. Issue 1 (25th March 2019) - Miles, Sam
Abstract : This paper explores the co‐construction of a temporary yet intimate relationship between researcher and participant when discussing participants' personal lives in fieldwork interviews. Through the case study of a project exploring how men who have sex with men use geolocative mobile phone apps for social and sexual encounter, I explore how the researcher and participant can experience moments of striking intimacy while maintaining personal and professional boundaries. The paper contributes to sex and sexualities research by arguing that intimacy can be cohered spatially and in limited timeframes, contrary to critical approaches suggesting that longer term and more intimately involved ethnographies are necessary for rich empirical results. In an environment of restrictive institutional ethical norms, this paper provides a methodological road‐map for scaffolding an environment for intimate relating that maximises participant engagement while managing (inter)personal boundaries. Abstract : This paper explores the co‐construction of a temporary yet intimate relationship between researcher and participant when discussing participants' personal lives in fieldwork interviews. Through the case study of a project exploring how men who have sex with men (MSM) use geolocative mobile phone apps for social and sexual encounter, I explore how the researcher and participant can experience moments of striking intimacy while maintaining personal and professional boundaries. The paper contributes to sex and sexualities research by arguing that intimacy can be cohered spatially and in limited timeframes, contrary to critical approaches suggesting that longer term and more intimately involved ethnographies are necessary for rich empirical results. In an environment of restrictive institutional ethical norms, this paper provides a methodological road‐map for scaffolding an environment for intimate relating that maximises participant engagement while managing (inter)personal boundaries.